HUBUNGAN RIWAYAT ANSIETAS DI KELUARGA TERHADAP ANSIETAS MAHASISWA TINGKAT I DALAM MEMPERTAHANKAN BEASISWADI AKPER MANGGALA HUSADA - Sri Laela (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2018)
Level I students who receive scholarships are at risk of experiencing anxiety, this is because students are experiencing environmental changes from high school to college and must be able to maintain their scholarships. The aim of this research is to identify the relationship between the history of anxiety in the family and the anxiety of level I students in maintaining their scholarship at the Manggala Husada Academy. The research method used was a quasi-experiment with control group pretest – posttest design with a consecutive sampling method. The sample in this study was 48 respondents. This study used the Zung Self - rating Anxiety Scale (ZSAS) questionnaire. The results of the research show that there is a strong relationship between the history of anxiety in the family and the anxiety of level I students in maintaining their scholarship at the Manggala Husada Academy. There was a significant decrease in anxiety (p-value = 0.000) in the group that received nurse nursing and thought stopping therapy. There was a decrease in the same level of anxiety in the group that received nurse care and the group that received nurse care and thought stopping therapy. Nurses' nursing actions and thought stopping therapy are able to reduce student anxiety with scholarships.